Treatment of children's sleep problems and its effect on maternal mental health - El Rafihi-Ferreira, Renatha; Pires, Maria Laura Nogueira [UNESP]; Mastroeni, Marco Fabio; Silvares, Edwiges Ferreira de Mattos (Routledge Journals, Taylor & Francis Ltd, 2020)
The aim of this study was to investigate the effect of a behaviour intervention for child sleep problems on the mother's internalizing behaviour. Sixty-two mothers who participated in an intervention for childhood insomnia through a programme designed for parents were evaluated using the Adult Self Report. Assessments were conducted one week before and one week after treatment completion. The child sleep problem score and mother internalizing behaviour score were significantly lower after the treatment of child sleep problems when compared to the pre-treatment period. However, adjusted analyses demonstrated that only maternal adaptive functioning continued to exert a significant and independent effect on the mother's internalizing behaviour even after adjustment for maternal age and child sleep problems (beta = -0.518; p < 0.01). The current study demonstrated that a behavioural intervention for improving child sleep problems through a programme designed for parents also benefited the mother's internalizing behaviour.
Keywords: Sleep; behavioural intervention; mental health; children; mother